Cogito, ergo praedico (I think, therefore I predict). (September 2021) - Lepping, Peter
SUMMARY: I comment on a new overview of the treatment of delusional infestation. I focus on the challenges of communicating with a patient who has delusions and evaluate practical advice. I look at philosophical models to explain those communication problems as well as theories of delusional formation, and examine how these may help clinicians to understand and overcome those challenges.